Jesus' Journey to Jerusalem (Luke 9.51-19.46): a Conflict with Israel - Matera, Frank J. 1942- (1993)
After reviewing the problems presented by Luke's journey narrative (9.51-19.46), this essay proposes to view the Lukan journey from a literary-critical perspective. It proposes that the Lukan narrator often employs changes of time and place to intro duce discourses by Jesus to the disciples, the crowd and the religious leaders. An examination of these discourses, which make up the bulk of the journey narrative, discloses the conflicting points of view espoused by Jesus on the one hand, and the crowd and its religious leaders on the other hand. Jesus' conflict with Israel, as he journeys to Jerusalem, helps to explain his rejection at Jerusalem.